Psychosomatic Symptoms Among Young Carers: A Population-Based Survey in Finland - Eronen-Levonen, Ella; Pasanen, Miko; Mishina, Kaisa; Leu, Agnes; Suhonen, Riitta; Joronen, Katja (United Kingdom, 2026)
Background
Young carers provide significant care for their significant others, and this group of people is often hidden in schools and society. Previous research has shown that young carers face several wellbeing deficits. There is little nationally representative research on the health of this vulnerable group of young people.
Aims
This study first examined how young carer background is associated with psychosomatic symptoms among 16–18-year-olds in a general population. Secondly, the study analysed how young carer background and socio-demographic variables explain psychosomatic symptoms when confounding factors are controlled.
Methods
The data source was the School Health Promotion (SHP) study, a nationwide self-report survey of students (n = 61,448) in upper secondary and vocational schools in Finland. Chi-squared tests and logistic regression analyses were carried out.
Results
Almost 9% of the students had experiences of caring relationships at least monthly, and 5% at least weekly. Psychosomatic symptoms were more frequent among 16–18-year-old students who had caring responsibilities at least weekly than among those who had caring responsibilities monthly or less often. In addition, several socio-demographic variables such as female gender, economic situation of the family, living with only one or without parents, and confounding factors, that is, self-perceived health and anxiety, were associated with psychosomatic symptoms. After controlling for all factors, this study found that a caring relationship was still associated with a higher frequency of perceived psychosomatic symptoms.
Conclusions
These findings could promote professionals in health promotion, health care, and education, to be more aware of the existence and support needs of young people with caring responsibilities.